Risk of Material Misstatement, Supply Chain Management and Audit Liability in Economy Development - Parno Suwito, Triyanto; Mohamed, Nafsiah; Abdullah, Azizah; Irianto, Gugus (International Journal of Supply Chain Management, 2020)
Abstract— In today’s complex connected world, supply chain is more and more recognised as a key source of competitive advantage and differentiation. Companies strive to build powerful supply chains that will enable them to get their products to market faster, more efficiently and more economically than their competition. The auditor should provide judgment with professionals, but empirical findings indicate the auditor is influenced by supply chain managements that can the determination of risk of material misstatement. With the fraud found in several large companies in Indonesia that have received reasonable opinions without exceptions, the auditor is accused of not professionally determining risk of material misstatement. The purpose of this study is to investigate the auditor's views on the allegations of failure of audit judgment when the client receives a reasonable opinion without exception but later it is proven that the client is cheating financial statements. This research also aims to explore supply chain managements that have the potential to influence the determination of the auditor's risk of material misstatement in the auditor's legal obligations related to fraud detection. The novelty of this research is in the search for factors that influence auditor judgment in the form of risk of material misstatement. Previous research in behavioral aspects in the context of the audit examined the auditor's judgment in terms of audit opinion as well as fraud risk assessment. Risk of material misstatement is relevant in explaining the various phenomena that accuse auditors when fraud is found in companies that have been given a fair opinion without exception. The study design was employed Qualitative methods using interview techniques with several key informants. Resource persons who act as informants are CPA firm partners who are partners in the big ten in Indonesia. The results showed that the supply chain managements that caused the auditor not to determine professional judgment in the form of risk of material misstatement were auditor's lack of skepticism, individual bias, lack of training and lack of supervision from the audit manager during fieldwork. The results of this research can be used by the Indonesian Institute of Certified Public Accountants in conducting training that is able to improve the quality and capability of auditors to improve the ability to formulate risk of material misstatement.